ONLINE DISCUSSION STRATRGIES TO FACILITATE STUDENTS DISCUSSION FOR A SPECIFIC ACADEMIC PURPOSES COURSE AT A TECHNICAL ENGINEERING UNIVERSITY - Azura Binti Omar; Nor Farizah Binti Mohd Taib (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2022)
At higher education institutions, hybrid learning that incorporates digital classroom and online teaching and learning activities are becoming increasingly popular norms. Throughout the academia, the usage of online discussion forums is progressively making its way into language classroom as studies have shown that it contributes to a good learning environment if efficiently used by both learners and educators. This qualitative study investigated strategies used by undergraduates as purposive samples in planning and executing ideas for a project via online discussion mode. This simple case study involved 15 second semester undergraduates taking â€œProfessional English 1â€ course in Bachelor in Engineering Technology program. A focus group interview and follow-up individual interviews were used to elicit information from the undergraduates. All these were also triangulated with document analysis of their reflective notes and drafts of writing works. Several questions were asked to the undergraduates during both interviews to determine their strategies when discussing online. The findings indicate that participants have tremendously benefited from online discussions and have employed three main strategies namely 1) asking for clarification, 2) going over previous responses and 3) using free online services and websites. This study provides useful insight and increases awareness among lecturers on the online discussion strategies used by students, allowing for more successful and meaningful planning of tasks involving online discussion.